2008
DOI: 10.1038/sj.cdd.4402307
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex III regulates hypoxic activation of HIF

Abstract: Decreases in oxygen levels are observed in physiological processes, such as development, and pathological situations, such as tumorigenesis and ischemia. In the complete absence of oxygen (anoxia), mammalian cells are unable to generate sufficient energy for survival, so a mechanism for sensing a decrease in the oxygen level (hypoxia) before it reaches a critical point is crucial for the survival of the organism. In response to decreased oxygen levels, cells activate the transcription factors hypoxiainducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
315
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(332 citation statements)
references
References 64 publications
13
315
1
3
Order By: Relevance
“…Mitochondria increase their generation of ROS through complex III during hypoxia. 9 These ROS participate in signal transduction pathways involved in adaptive responses, including ischemic preconditioning and gene transcription. Damaged mitochondria increase ROS production, resulting in the accumulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria increase their generation of ROS through complex III during hypoxia. 9 These ROS participate in signal transduction pathways involved in adaptive responses, including ischemic preconditioning and gene transcription. Damaged mitochondria increase ROS production, resulting in the accumulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been suggested that the electron transport chain functions as an O 2 sensor by releasing reactive oxygen species (ROS) from complex III in response to hypoxia. 8,9 Oxidative stress increases with aging, and the accumulation of oxidative damage to mitochondrial DNA appears to be involved in the aging phenotype. Thus, impairment of mitochondria in response to oxidative stress accumulation may decrease mitochondrial oxygen sensing.…”
mentioning
confidence: 99%
“…Angiogenesis owing to VEGF-A action allows tumors to obtain nutrients to sustain their metabolism during their uncontrolled growth (Semenza, 2010;Cairns et al, 2011). 2008). Both ROS and hypoxia itself inhibit prolyl hydroxylase activity, rescuing HIF-1 (Klimova and Chandel, 2008). Strikingly, TP53 knockout (Ravi et al, 2000) and c-MYC overexpression (Shim et al, 1997) also increase HIF-1 activity.…”
Section: Bioenergetics and The Tumor Microenvironmentmentioning
confidence: 99%
“…Indeed, mutations in FH (Isaacs et al 2005) and SDH (Pollard et al 2005;Frezza et al 2011) are observed in renal cancers, paragangliomas, and pheochromocytomas. Additionally, mitochondrial reactive oxygen species (ROS) generated from complex III of the electron transport chain (ETC) also regulate hypoxic activation of Hif-1a (Klimova and Chandel 2008) and hypoxia-responsive gene expression. Thus, the metabolic state of a cell can also control its regulatory state, indicating a dynamic and reciprocal relationship between the two.…”
Section: Cancer Is a Metabolic Diseasementioning
confidence: 99%